Preparation method of barium carbonate powder

By using barium nitrate and ammonium bicarbonate as raw materials, high-purity ultrafine BaCO3 powder was prepared by metathesis method, which solved the problem of excessive particle size and high chloride ion content in traditional methods, achieved a more uniform particle size distribution and a larger specific surface area, and improved the quality of the product.

CN119873868APending Publication Date: 2025-04-25SOUTHWEAT UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510101310.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The average particle size of BaCO3 powder produced by traditional methods is usually above 5 μm, which cannot meet the requirements for use of precision electronic components. At the same time, in the domestic high-end BaCO3 production, barium chloride as a source of barium leads to a high chloride ion content in the product, which is difficult to control and affects quality.

Method used

Barium nitrate (Ba(NO3)2) is used as the barium source and ammonium bicarbonate (NH4HCO3) is used as the carbon source to prepare high-purity ultrafine BaCO3 powder by metathesis method, combined with magnetic stirring, stand-alt precipitation, filtration and washing, and vacuum drying.

Benefits of technology

The prepared BaCO3 powder has a more uniform particle size distribution and a larger specific surface area, which meets the needs of high-purity ultrafine powders, avoids the problem of high chloride ion content, and improves the quality of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119873868A_ABST
    Figure CN119873868A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of barium carbonate powder. The preparation method comprises the following steps: respectively preparing a Ba (NO3) 2 solution and an NH4HCO3 solution by using deionized water; the preparation method comprises the following steps: dropwise adding an NH4HCO3 solution into a Ba (NO3) 2 solution under magnetic stirring, stopping magnetic stirring after the NH4HCO3 solution is dropwise added, and standing and precipitating the solution; and filtering and collecting the precipitate, washing the precipitate with deionized water during filtering, and carrying out vacuum drying to obtain the barium carbonate powder. According to the preparation method, barium nitrate is taken as a barium source, ammonium bicarbonate is taken as a carbon source, high-purity superfine BaCO3 powder is prepared through a double decomposition method, and the high-purity superfine BaCO3 powder has a witherite configuration, shows a granular structure which is uniformly distributed in a range of 100nm-200nm, and not only has more uniform particle size distribution, but also has a larger specific surface area.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of barium carbonate preparation, and more specifically, relates to a method for preparing barium carbonate powder. Background Art

[0002] Barium carbonate (BaCO3) is an important heavy metal carbonate. It is widely used in optical glass, magnetic materials, pigments, barium salts and electronic additive materials due to its high thermodynamic stability and strong crystal modification effect. The outstanding applications of BaCO3 include: relying on its X-ray shielding ability, it can be used as a glass shell material in cathode ray tubes to absorb X-rays generated under high voltage current; BaCO3 powder can significantly improve the hardness and corrosion resistance of ceramic materials such as tiles; BaCO3 powder can also be used as an additive in the preparation process of glass to improve the pourability, hardness and refractive index of glass. BaCO3 powder is highly valued by researchers due to its excellent physical and chemical properties and wide range of applications.

[0003] With the rapid development of science and technology, the requirements for the purity and particle size of BaCO3 powder materials in the fields of electronic chemical industry are getting higher and higher. The average particle size of BaCO3 powder materials produced by traditional methods is usually above 5μm, which cannot meet the use requirements of precision electronic components. In order to meet the needs of practical applications, high-purity ultrafine BaCO3 with advantages such as low loss and high dielectric constant has been developed to replace traditional BaCO3 powder materials. Although China is the largest producer of BaCO3, the high-end BaCO3 required by the domestic market still mainly relies on overseas imports. At present, the high-end BaCO3 that has been industrialized in China mainly uses barium chloride (BaCl2) as a barium source, and the large-scale production of BaCO3 is achieved by reacting it with ammonium carbonate after dissolution. Although this method has been able to produce BaCO3 on a large scale, the chloride ion content of the produced BaCO3 is high and difficult to control, which seriously affects the quality of high-end BaCO3. Therefore, it is very necessary to develop a new high-purity ultrafine BaCO3 preparation scheme. Summary of the invention

[0004] An object of the present invention is to solve at least the above problems and / or disadvantages and to provide at least the advantages which will be described hereinafter.

[0005] In order to achieve these objects and other advantages of the present invention, a method for preparing barium carbonate powder is provided, comprising the following steps:

[0006] Step 1: Use deionized water to prepare Ba(NO3)2 solution and NH4HCO3 solution respectively;

[0007] Step 2: Under magnetic stirring, add NH4HCO3 solution to the Ba(NO3)2 solution. After the addition of NH4HCO3 solution is completed, stop magnetic stirring and let the solution stand to settle;

[0008] Step 3: Filter and collect the precipitate, wash the precipitate with deionized water during filtration, and vacuum dry to obtain barium carbonate powder.

[0009] Preferably, in step 1, the concentration of the Ba(NO3)2 solution is 0.005-0.02 mol / L.

[0010] Preferably, in step 1, the concentration of the NH4HCO3 solution is 0.005-0.02 mol / L.

[0011] Preferably, in step 2, the rotation speed of the magnetic stirring is 200 to 500 rpm.

[0012] Preferably, in step 2, the molar ratio of Ba(NO3)2 to NH4HCO3 is 1:1-3.

[0013] Preferably, in step 2, the solution is allowed to settle for 50 to 100 minutes.

[0014] Preferably, in step 3, the precipitate is washed with deionized water 2 to 5 times; and the vacuum drying temperature is 50 to 70°C.

[0015] Preferably, the step 2 is replaced by: adding NH4HCO3 solution to the Ba(NO3)2 solution under magnetic stirring, stopping the magnetic stirring after the addition of NH4HCO3 solution is completed, subjecting the obtained solution to electromagnetic oscillation treatment for 10 to 20 minutes, and allowing the solution to settle for 10 to 30 minutes.

[0016] Preferably, the specific method of electromagnetic oscillation treatment is: the medium-low duty cycle is 25-35%, firstly 20-50 Hz high frequency electromagnetic oscillation treatment is carried out for 3-8 minutes, and then 0.5-3 Hz low frequency electromagnetic oscillation treatment is carried out for 5-15 minutes.

[0017] A method for preparing barium carbonate powder comprises the following steps:

[0018] Step 1, add BaCl2, CO(NH2)2 and NaOH into deionized water to make the concentration of BaCl2 be 0.5-1.5 mol / L, heat in an oil bath for reaction, and cool naturally to room temperature to obtain a product;

[0019] Step 2: Use a vacuum filtration device to separate the barium carbonate solid from the product obtained in step 1, and dry the filtered solid in an oven at 50-70° C. to obtain barium carbonate powder.

[0020] Preferably, in step 1, the molar ratio of BaCl2, CO(NH2)2 and NaOH is 1:5-7:2-3.

[0021] Preferably, in step 1, the specific method of the oil bath heating reaction is: heating the oil bath to 70-90° C., controlling the rotation speed to 200-500 rpm, maintaining for 5-7 hours and then stopping the heating.

[0022] The present invention has at least the following beneficial effects:

[0023] 1. The present invention uses barium nitrate (Ba(NO3)2) as a barium source and ammonium bicarbonate (NH4HCO3) as a carbon source to prepare high-purity ultrafine BaCO3 powder (BaCO3-N) by a double decomposition method. The powder has a witherite configuration and shows a granular structure uniformly distributed in the range of 100nm-200nm. Compared with BaCO3 powder (BaCO3-Cl) prepared using barium chloride (BaCl2) as a barium source, BaCO3-N not only has a more uniform particle size distribution, but also has a larger specific surface area. The barium nitrate-ammonium bicarbonate double decomposition method developed by the present invention will provide a new solution for preparing high-purity ultrafine barium carbonate powder.

[0024] 2. The present invention uses barium chloride as a barium source and uses a mild homogeneous precipitation method to prepare barium carbonate with high purity. The prepared BaCO3 powder (BC2) belongs to orthorhombic phase barium carbonate, and its specific surface area meets the standard of superior products, which is comparable to barium hydroxide (Ba(OH )2 ) as the barium source, BC2 has a more uniform particle size distribution and a larger specific surface area.

[0025] Other advantages, objectives and features of the present invention will be embodied in part through the following description, and in part will be understood by those skilled in the art through study and practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The SEM images and EDS mapping spectra of BC2 prepared in Example 1 and BC1 prepared in Comparative Example 2, wherein (a) and (b) are SEM images of BC1, (c) is the EDS mapping spectrum of the corresponding position of BC1, (d) and (e) are SEM images of BC2, and (f) is the EDS mapping spectrum of the corresponding position of BC2;

[0027] Figure 2 XRD patterns (a) and FTIR spectra (b) of BC2 prepared in Example 1 and BC1 prepared in Comparative Example 2;

[0028] Figure 3XPS spectra of BC2 prepared in Example 1 and BC1 prepared in Comparative Example 2 (a), high-resolution XPS spectra of Ba 3d (b), C 1s (c), and O1s (d);

[0029] Figure 4 FTIR spectra (a) and XRD patterns (b) of BaCO3-N prepared in Example 2 and BaCO3-Cl prepared in Comparative Example 2;

[0030] Figure 5 XPS spectra of BaCO3-N prepared in Example 2 and BaCO3-Cl prepared in Comparative Example 2 (a), high-resolution XPS spectra of C 1s (b), O1s (c) and Ba 3d (d);

[0031] Figure 6 The SEM images of BaCO3-N prepared in Example 2 and BaCO3-Cl prepared in Comparative Example 2, wherein (a) and (b) are SEM images of BaCO3-Cl, and (c) and (d) are SEM images of BaCO3-N;

[0032] Figure 7 These are the EDS mapping spectra of BaCO3-N prepared in Example 2 and BaCO3-Cl prepared in Comparative Example 2, wherein (a) is the EDS mapping spectrum of BaCO3-Cl, and (b) is the EDS mapping spectrum of BaCO3-N. DETAILED DESCRIPTION

[0033] The present invention is further described in detail below in conjunction with the accompanying drawings so that those skilled in the art can implement the invention with reference to the description.

[0034] It should be understood that terms such as “having”, “including” and “comprising” used herein do not exclude the existence or addition of one or more other elements or combinations thereof.

[0035] In the following examples, the raw materials and reagents used are: barium chloride (BaCl2, 99.9%), barium hydroxide (Ba(OH)2, 99.9%), urea (CO(NH2)2) and sodium hydroxide (NaOH) were all purchased from Chengdu Cologne Company, barium nitrate (Ba(NO3)2, 99.5%), barium chloride (BaCl2, 99.9%) and ammonium bicarbonate (NH4HCO3, 99%) were all purchased from Aladdin Biochemical Technology Co., Ltd. (Shanghai, China), the sample dispersant used was deionized water, and all chemical reagents were of analytical grade and no additional treatment was required.

[0036] Example 1

[0037] A method for preparing barium carbonate powder comprises the following steps:

[0038] Step 1: Add BaCl2, CO(NH2)2 and NaOH in a molar ratio of 1:6:2.5 into an aluminum cap bottle containing 40 mL of deionized water, wherein the concentration of BaCl2 is 1.0 mol / L, heat in an oil bath at 80°C, control the speed to 300 rpm, keep heating for 6 hours, then stop heating, and cool naturally to room temperature to obtain the product;

[0039] Step 2: Use a vacuum filtration device to separate the barium carbonate solid from the product obtained in step 1, and dry the filtered solid in an oven at 60° C. to obtain barium carbonate powder (BC2) with a purity of 99.9%.

[0040] Comparative Example 1

[0041] A method for preparing barium carbonate powder comprises the following steps:

[0042] Step 1: Add Ba(OH)2, CO(NH2)2 and NaOH in a molar ratio of 1:6:2.5 into an aluminum cap bottle containing 40 mL of deionized water, wherein the concentration of Ba(OH)2 is 1.0 mol / L, heat in an oil bath at 80°C, control the speed to 300 rpm, keep heating for 6 hours, then stop heating, and cool naturally to room temperature to obtain the product;

[0043] Step 2: Use a vacuum filtration device to separate the barium carbonate solid from the product obtained in step 1, and dry the filtered solid in an oven at 60° C. to obtain barium carbonate powder (BC1) with a purity of 98.7%.

[0044] like Figure 1As shown, (a) and (b) are SEM images of BC1, (c) is the EDS mapping spectrum of the corresponding position of BC1, (d) and (e) are SEM images of BC2, and (f) is the EDS mapping spectrum of the corresponding position of BC2. Comparing the surface micromorphology of samples BC1 and BC2 (Figures (a) and (d)) at a scale of 1μm, it can be seen that the surface morphology of the barium carbonate powder BC1 prepared using Ba(OH)2 as the barium source is quite different, with large and small barium carbonate agglomerated microspheres and a small amount of needle-shaped barium carbonate particles. It is obvious that the micromorphology of the synthesized barium carbonate powder is not uniform and has different shapes; while the surface morphology of the barium carbonate powder BC2 prepared using BaCl2 as the barium source is obviously more uniform, and the size of the spherical barium carbonate nanoparticles is basically similar; when the surface micromorphology of the two samples is compared at a scale of 400nm, it can be seen that the distribution of barium carbonate nanoparticles on the surface of BC2 microspheres is also more uniform (Figures (b) and (e)). Comparing the element distribution of the two products from their EDS Mapping diagrams, it can be seen that the distribution of elements in BC2 is also more uniform, especially Ba as the main element.

[0045] The XRD patterns of BC1 and BC2 are shown in Figure 2 As shown in a, it can be seen that the diffraction peak of BC2 is sharper than that of BC1, and BC1 has more burrs, which proves that the crystallinity of sample BC2 is higher and less amorphous products are generated. The obvious diffraction peak positions of the BC2 spectrum correspond to (011), (111), (200), (112), (103), (220), (221), (132), (113), (311), (241), (151), (114), and (204) crystal planes, which are in good agreement with the PDF standard card 041-0373 orthorhombic phase barium carbonate diffraction data. There are basically no impurity diffraction peaks, indicating that the obtained sample is pure BaCO3 and the purity and crystallinity of the product are also high.

[0046] Figure 2 b shows the wavelength between 500-4000cm -1 The Fourier transform infrared spectrum in the range shows that at a wavelength of 3500cm -1 The absorption peaks on the left and right are caused by the stretching vibration of hydroxyl -OH, which is related to the drying of the sample and the adsorption of a small amount of water in the air on its surface; wavelength 1450cm -1 The strong absorption peaks appearing around 1100cm -1 The absorption peaks on the left and right represent the asymmetric stretching vibration of the CO bond in the orthorhombic BaCO3 crystal; the absorption peak formed by the bending vibration of the carbonate group is at a wavelength of 850cm -1 With 690cm -1The functional group composition further confirmed that the samples prepared by the two methods were BaCO3 crystals, and the absorption peaks of each functional group were typical characteristic peaks, and no new characteristic peaks appeared. Therefore, it can be shown that BC1 and BC2 were successfully prepared, and the choice of barium source had no effect on the functional groups of the prepared BaCO3 powder.

[0047] like Figure 3 As shown in the figure, the quantitative analysis of each element of barium carbonate prepared from the two raw materials by XPS shows that the 3d 3 / 2 Tracks and 3D 5 / 2 The binding energies of the orbitals are 795.1 and 779.8 eV respectively, and the corresponding orbital binding energies of BC2 are 795.4 and 780.0 eV; the 3d 3 / 2 Tracks and 3D 5 / 2 The binding energies of the orbitals are at 795.1 and 779.8 eV, respectively, and the corresponding orbital binding energies of BC2 are at 795.4 and 780.0 eV; the binding energy peak of the C1s element of BC1 at 284.8 eV can be attributed to CO3 2- The peak at 289.0 eV can be attributed to the -OC- bond of CO3 2- The OCO bond of BC1 and the corresponding orbital chemical bond binding energies of BC2 are at 289.3 and 284.8 eV respectively. In addition, there is one more binding energy peak at 297.1 eV compared with BC1, which is due to the π-π bond formed by the C elements side by side. The binding energy peak of the O1s element of BC1 is at 531.2 eV, and the corresponding orbital binding energy of BC2 is at 531.6 eV. The data results of XPS spectrum show that BC1 and BC2 have similar composition structures, but during the formation of BC2, the C element also has a π-π bond that does not exist in BC1.

[0048] The specific surface area of ​​the solid powder was determined by the BET method, and the results are shown in Table 1. According to the BET test, the specific surface area of ​​the BC1 sample is 3.7142 m 2 / g, the specific surface area of ​​BC2 sample is 6.1973m 2 / g, BC2 samples meet GB / T1614-1999 superior products (4~8m 2 The comparison of BET test shows that the micropore area and void volume of the two samples are also larger in the BC2 sample, which proves that the BC2 material has a smaller particle size and more uniform particle distribution.

[0049] Table 1

[0050]

[0051] The results show that the orthorhombic barium carbonate BC2 prepared by homogeneous synthesis using BaCl2 as a barium source and NaOH and CO(NH2)2 has better effects and higher product quality than the barium carbonate BC1 synthesized using Ba(OH)2 as a barium source. From the results of SEM, it can be seen that the surface morphology of the barium carbonate powder BC2 prepared by BaCl2 as a barium source is obviously more uniform, and the mapping diagram shows that the element distribution of Ba in BC2 is also more uniform. Through XRD, it can be seen that the crystallinity of the sample BC2 is higher, and the generated amorphous products are less, and the peak position is more consistent with the standard card. FTIR can prove that the products synthesized from the two raw materials are both barium carbonate. Through BET, it can be intuitively concluded that the specific surface area of ​​the BC2 sample is larger and meets the standards of superior products. The present invention provides a relatively convenient and low-cost way for large-scale synthesis of such small-sized nano-scale products.

[0052] Example 2

[0053] A method for preparing barium carbonate powder comprises the following steps:

[0054] Step 1: Use deionized water to prepare 0.01 mol / L Ba(NO3)2 solution and 0.01 mol / L NH4HCO3 solution, then take out a certain volume of Ba(NO3)2 solution and place it in a 200 mL empty beaker;

[0055] Step 2: Slowly add NH4HCO3 solution to the Ba(NO3)2 solution at a molar ratio of Ba(NO3)2 to NH4HCO3 of 1:2, accompanied by magnetic stirring at a speed of 300 rpm. After the addition of NH4HCO3 solution is completed, stop the magnetic stirrer and let the solution stand for 60 minutes;

[0056] Step 3: Filter and collect the precipitate. During the filtration, wash the precipitate three times with deionized water and dry it in vacuum at 60° C. The obtained white solid is barium carbonate powder (BaCO3-N) with a purity of 99.9%.

[0057] Comparative Example 2

[0058] A method for preparing barium carbonate powder comprises the following steps:

[0059] Step 1: Use deionized water to prepare 0.01 mol / L BaCl2 solution and 0.01 mol / L NH4HCO3 solution respectively, then take out a certain volume of BaCl2 solution and place it in a 200 mL empty beaker;

[0060] Step 2: Slowly add NH4HCO3 solution to the BaCl2 solution at a molar ratio of BaCl2 to NH4HCO3 of 1:2, accompanied by magnetic stirring at a speed of 300 rpm. After the addition of NH4HCO3 solution is completed, stop the magnetic stirrer and let the solution stand for 60 minutes;

[0061] Step 3: Filter and collect the precipitate. During the filtration, wash the precipitate three times with deionized water and dry it in vacuum at 60° C. The obtained white solid is barium carbonate powder (BaCO3-Cl) with a purity of 99.5%.

[0062] Figure 4 a shows the wavelength between 500-4000cm -1 From the FTIR spectra of BaCO3-Cl and BaCO3-N, it can be observed that the -1 and 693cm -1 The absorption band at 2- Stretching vibration. At 450-1800cm -1 In the range of 1411 cm-1, the -CO- stretching vibration peaks appeared in the FTIR spectra of BaCO3-Cl and BaCO3-N. -1 The characteristic peaks observed at 2- In addition, the OH stretching vibration and HOH bending vibration correspond to 3000-3800cm -1 Wide band and 1750-1630cm -1 Broadband. From the results of FTIR spectra, it can be seen that BaCO3-Cl and BaCO3-N were successfully prepared, and the choice of barium source had no effect on the functional groups of the prepared BaCO3 powder.

[0063] The XRD patterns of BaCO3-Cl and BaCO3-N are as follows Figure 4The XRD patterns of BaCO3-Cl and BaCO3-N both show characteristic peaks at 19.4°, 23.9°, 24.3°, 27.7°, 29.5°, 33.7°, 34.1°, 34.4°, 34.6°, 39.5°, 42.0°, 43.1°, 44.2°, 44.9°, 46.8° and 47.0°, which correspond to (110), (111), (021), (002), (012), (200), (112), (130), (220), (221), (041), (202), (132), (113) and (023) of witherite crystal form BaCO3, respectively. The results show that both BaCO3-Cl and BaCO3-N prepared by the ammonium carbonate double decomposition method present a single crystal structure (witherite crystal form), and the crystal structure is not affected by the barium source material.

[0064] XPS spectra were used to study the composition of BaCO3-Cl and BaCO3-N powders. Figure 5 a shows the full XPS spectra of BaCO3-Cl and BaCO3-N, from which it can be observed that both BaCO3-Cl and BaCO3-N have peaks of C1s, O 1s and Ba 3d. Figure 5 The high-resolution C1s spectrum shown in b can be fitted into three peaks, of which 284.7 eV is the energy spectrum peak of the standard background C1s, and the peak at 285.6 eV is attributed to CO3 2- The peak at 289.4 eV can be attributed to the -OC- bond of CO3 2- OCO bond. Figure 5 As shown in c, the O1s region can be fitted into two different peaks at 531.5 and 532.4 eV, which correspond to CO3 2- The CO bonds in the particles and the -OH bonds on the adsorbed water on the particle surface. Figure 5 d, the peaks at 795.5 and 780.2 eV can be classified as Ba 3d 3 / 2 and Ba3d 5 / 2 In addition, the peak at 790.1 eV is also consistent with the binding energy of Ba 3d 3 / 2 The XPS spectrum data results show that BaCO3-Cl and BaCO3-N have similar composition structures.

[0065] In order to explore the effect of barium source materials on the microstructure of BaCO3 powder materials, SEM images of BaCO3-Cl and BaCO3-N were obtained by SEM characterization, such as Figure 6 As shown, (a) and (b) are BaCO3-Cl, (c) and (d) are BaCO3-N. For BaCO3-Cl powder prepared with BaCl2 as barium source, Figure 6 a shows that the BaCO3-Cl powder has a structure with large particles tightly packed. Figure 6 b In the high-magnification SEM image, it can be observed that BaCO3-Cl is precisely stacked with particles with a particle size of more than 300nm and has a relatively small pore structure. Figure 6 The BaCO3-N powder prepared with Ba(NO3)2 as the barium source in c shows a more uniform distribution of small particles. Figure 6 It can be clearly observed in d that the particle size distribution of BaCO3-N particles is in the range of 100-200nm, and has a relatively large porous structure. The SEM image results show that the BaCO3 powder prepared with BaCl2 as the barium source has a larger particle size and a more compact particle stacking, while the BaCO3 powder prepared with Ba(NO3)2 as the barium source has a smaller particle size and a more uniform particle distribution. For the preparation of high-purity ultrafine BaCO3 powder, Ba(NO3)2 may have more advantages as a barium source than BaCl2.

[0066] Figure 7 The EDS mapping spectra of BaCO3-Cl and BaCO3-N are shown, where (a) is BaCO3-Cl and (b) is BaCO3-N. The spectra show that both BaCO3-Cl and BaCO3-N have C, O and Ba elements on their surfaces. By comparing the distribution of C and O elements in the EDS mapping spectra of BaCO3-Cl and BaCO3-N, it can be found that the distribution of C and O elements in BaCO3-Cl is more concentrated, while the distribution of C and O elements in BaCO3-N is more uniform, which may be attributed to the closer stacking of BaCO3-Cl particles. In contrast, there is no obvious difference in the distribution of Ba elements in the EDS mapping spectra of the two samples. The element distribution of the EDS mapping spectra further proves the successful preparation of BaCO3-Cl and BaCO3-N powders. In addition, the specific surface areas of BaCO3-Cl and BaCO3-N powders were detected by BET surface area analyzer, and the test results are shown in Table 2. The BET surface area and pore volume of BaCO3-Cl are 1.6886 m 2 / g and 0.000953cm 3 / g, while the BET surface area and pore volume of BaCO3-N are 2.7687m 2 / g and 0.001497cm 3 / g. The results show that BaCO3-N has a larger BET surface area and pore volume than BaCO3-Cl, which may be related to its smaller particle size and uniform particle distribution. The BET surface area and pore volume results once again prove that Ba(NO3)2 is a more advantageous barium source material in the preparation of high-purity ultrafine BaCO3 powder by ammonium carbonate double decomposition.

[0067] Table 2

[0068] Sample <![CDATA[BET Surface Area(m 2 / g)]]> <![CDATA[Pore Volume(cm 3 / g)]]> <![CDATA[BaCO3-Cl]]> 1.6886 0.000953 <![CDATA[BaCO3-N]]> 2.7687 0.001497

[0069] In summary, the present invention successfully uses Ba(NO3)2 as a barium source and NH4HCO3 as a carbon source to efficiently prepare high-purity ultrafine BaCO3-N powder by double decomposition method. Through characterization techniques such as FTIR, XRD, SEM, etc., it can be obtained that the prepared BaCO3-N powder has a witherite configuration and shows a granular structure uniformly distributed in the range of 100nm-200nm. In addition, compared with BaCO3-Cl powder (BaCO3-Cl) prepared with BaCl2 as a barium source, BaCO3-N not only has a more uniform particle size distribution, but also has a larger specific surface area. The results show that Ba(NO3)2 may be more suitable for preparing high-purity ultrafine BaCO3 powder by ammonium carbonate double decomposition method than BaCl2. Based on these results, it is an effective preparation scheme to prepare high-purity ultrafine BaCO3 powder by ammonium carbonate double decomposition method using Ba(NO3)2 as a barium source, which also provides ideas for further designing and optimizing the preparation process of high-purity ultrafine BaCO3 powder.

[0070] In Example 1, a homogeneous precipitation method is used to prepare high-purity barium carbonate powder, and in Example 2, a carbonate ammonium double decomposition method is used to prepare high-purity ultrafine barium carbonate powder. The purity of the barium carbonate powders of both examples is ≥99.9%. Among them, the barium carbonate powder of Example 1 has a higher specific surface area and pore volume, but a larger particle size. The specific surface area and pore volume of the barium carbonate powder of Example 2 are lower than those of Example 1, but its particle size is smaller and the particle size distribution is more uniform.

[0071] Example 3

[0072] A method for preparing barium carbonate powder comprises the following steps:

[0073] Step 1: Use deionized water to prepare 0.01 mol / L Ba(NO3)2 solution and 0.01 mol / L NH4HCO3 solution, then take out a certain volume of Ba(NO3)2 solution and place it in a 200 mL empty beaker;

[0074] Step 2: Slowly add NH4HCO3 solution to the Ba(NO3)2 solution at a molar ratio of Ba(NO3)2 to NH4HCO3 of 1:2, accompanied by magnetic stirring at a speed of 300 rpm. After the addition of NH4HCO3 solution is completed, stop the magnetic stirrer, and subject the obtained solution to electromagnetic oscillation treatment for 15 minutes, and let the solution stand and settle for 20 minutes; wherein the specific method of electromagnetic oscillation treatment is: the medium and low duty cycle is 30%, firstly subject to 32 Hz high-frequency electromagnetic oscillation treatment for 5 minutes, and then subject to 1 Hz low-frequency electromagnetic oscillation treatment for 10 minutes;

[0075] Step 3: Filter and collect the precipitate. During the filtration, wash the precipitate three times with deionized water and dry it under vacuum at 60° C. The obtained white solid is barium carbonate powder with a purity of 99.9%.

[0076] In this embodiment, electromagnetic oscillation treatment is used to promote the reaction, improve the efficiency of barium carbonate preparation, shorten the reaction precipitation time, and under the alternating action of high and low frequency electromagnetic fields, the microscopic morphology of the powder can be significantly affected. The obtained barium carbonate powder has a higher specific surface area and a smaller particle size. The specific surface area of ​​the barium carbonate powder obtained in Example 3 is 3.8255 m 2 / g, and the particle size distribution is in the range of 50nm-80nm.

[0077] Example 4

[0078] A method for preparing barium carbonate powder comprises the following steps:

[0079] Step 1: Use deionized water to prepare 0.01 mol / L Ba(NO3)2 solution and 0.01 mol / L NH4HCO3 solution, then take out a certain volume of Ba(NO3)2 solution and place it in a 200 mL empty beaker;

[0080] Step 2: Slowly add NH4HCO3 solution to Ba(NO3)2 solution at a molar ratio of Ba(NO3)2 to NH4HCO3 of 1:2, accompanied by magnetic stirring at a speed of 300 rpm. After the addition of NH4HCO3 solution is completed, stop the magnetic stirrer, and subject the obtained solution to electromagnetic oscillation treatment for 15 minutes, and let the solution stand and settle for 20 minutes; wherein the specific method of electromagnetic oscillation treatment is: medium and low duty cycle is 30%, and low frequency electromagnetic oscillation treatment is performed at 1 Hz for 15 minutes;

[0081] Step 3: Filter and collect the precipitate. During the filtration, wash the precipitate three times with deionized water and dry it in vacuum at 60°C. The obtained white solid is barium carbonate powder with a purity of 99.9% and a specific surface area of ​​3.0594 m 2 / g, and the particle size distribution is in the range of 100nm-200nm.

[0082] Example 5

[0083] A method for preparing barium carbonate powder comprises the following steps:

[0084] Step 1: Use deionized water to prepare 0.01 mol / L Ba(NO3)2 solution and 0.01 mol / L NH4HCO3 solution, then take out a certain volume of Ba(NO3)2 solution and place it in a 200 mL empty beaker;

[0085] Step 2: Slowly add NH4HCO3 solution to Ba(NO3)2 solution at a molar ratio of Ba(NO3)2 to NH4HCO3 of 1:2, accompanied by magnetic stirring at a speed of 300 rpm. After the addition of NH4HCO3 solution is completed, stop the magnetic stirrer, and subject the obtained solution to electromagnetic oscillation treatment for 15 minutes, and let the solution stand and settle for 20 minutes; wherein the specific method of electromagnetic oscillation treatment is: medium and low duty cycle is 30%, and high frequency electromagnetic oscillation treatment is performed at 32 Hz for 15 minutes;

[0086] Step 3: Filter and collect the precipitate. During the filtration, wash the precipitate three times with deionized water and dry it in vacuum at 60°C. The obtained white solid is barium carbonate powder with a purity of 99.9% and a specific surface area of ​​3.2643 m 2 / g, and the particle size distribution is in the range of 100nm-150nm.

[0087] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes, and they can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and the illustrations shown and described herein.

Claims

1. A method for preparing barium carbonate powder, characterized in that: The following steps are involved: Step 1: Use deionized water to prepare Ba(NO3)2 solution and NH4HCO3 solution respectively; Step 2: Under magnetic stirring, add NH4HCO3 solution to the Ba(NO3)2 solution. After the addition of NH4HCO3 solution is completed, stop magnetic stirring and let the solution stand to settle; Step 3: Filter and collect the precipitate, wash the precipitate with deionized water during filtration, and vacuum dry to obtain barium carbonate powder.

2. The method for preparing barium carbonate powder according to claim 1, characterized in that: In the step 1, the concentration of the Ba(NO3)2 solution is 0.005-0.02 mol / L.

3. The method for preparing barium carbonate powder according to claim 1, characterized in that: In the step 1, the concentration of the NH4HCO3 solution is 0.005-0.02 mol / L.

4. The method for preparing barium carbonate powder according to claim 1, characterized in that: In the step 2, the rotation speed of the magnetic stirring is 200 to 500 rpm.

5. The method for preparing barium carbonate powder according to claim 1, characterized in that: In the step 2, the molar ratio of Ba(NO3)2 to NH4HCO3 is 1:1-3.

6. The method for preparing barium carbonate powder according to claim 1, characterized in that: In the step 2, the solution is allowed to settle for 50 to 100 minutes.

7. The method for preparing barium carbonate powder according to claim 1, characterized in that: In the step 3, the precipitate is washed with deionized water for 2 to 5 times; and the vacuum drying temperature is 50 to 70°C.

8. A method for preparing barium carbonate powder, characterized in that: The following steps are involved: Step 1, add BaCl2, CO(NH2)2 and NaOH into deionized water to make the concentration of BaCl2 be 0.5-1.5 mol / L, heat in an oil bath for reaction, and cool naturally to room temperature to obtain a product; Step 2: Use a vacuum filtration device to separate the barium carbonate solid from the product obtained in step 1, and dry the filtered solid in an oven at 50-70° C. to obtain barium carbonate powder.

9. The method for preparing barium carbonate powder according to claim 8, characterized in that: In the step 1, the molar ratio of BaCl2, CO(NH2)2 and NaOH is 1:5-7:2-3.

10. The method for preparing barium carbonate powder according to claim 8, characterized in that: In the step 1, the specific method of the oil bath heating reaction is: heating the oil bath to 70-90° C., controlling the rotation speed to 200-500 rpm, maintaining for 5-7 hours and then stopping the heating.